Performance Optimization of Battery Balancing System Based on Multiwinding Transformer and Single Inductor with Fuzzy Logic Control Method - Yusiran, Yusiran; Leksono, Edi; Haq, Irsyad Nashirul; Ayumurti, Andini Jinggan (Master Program in Mechanical Engineering, Gunadarma University, 2025)
In this study, a modular battery balancing topology based on a single inductor and multi-winding transformer is proposed. In particular, the voltage equalization topology based on this modular balancer consists of cell-level equalization based on a multi-winding transformer and module-level equalization based on a single inductor. A control algorithm based on fuzzy logic (FLC) is applied to the module-level balancer with the difference between the module voltage and the module average voltage being used as the input variable and the duty cycle as the output variable. Meanwhile, the cell-level equalization utilizes a fixed duty cycle (FDC) control mechanism. The balancing process between cell and module level is done alternately so that this control method can be used on non-uniform transformers. The balancing model and FLC design was created in Matlab/Simulink 2021a and experiments using 4 cells LG HG2 18560 3000 mAh battery were carried out to verify the performance of the balancing system. The experimental results show that the FLC method can save the balancing time between modules by 31.26% compared to the FDC method. Furthermore, the proposed control system is proven to optimize the energy transfer which can reach zero voltage gap (ZVG) below 5 mV with a relatively high efficiency around 86.95%..